1993
DOI: 10.5694/j.1326-5377.1993.tb137821.x
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal symptoms in Australian women

Abstract: ObJectives: To describe Australian-born women's experience of symptoms during the natural menopause transition and the relative contribution of menopausal and health status, social factors and lifestyle behaviours.Design: A community based crosssectional survey by telephone Interview was carried out on a randomly derived sample of Melbourne women.Participants: The participants were 2000 Australian-born women, aged between 45 and 55 years. Outcome measures:A list of 22 symptoms was used. Explanatory variables w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
3
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(100 citation statements)
references
References 14 publications
6
86
3
4
Order By: Relevance
“…Although a number of studies have reported that women who smoke are more likely to report hot flushes, possibly due to the antiestrogenic effects of smoking (43, 47, 48), current smoking had no significant association with the duration of hot flushes in this cohort. Whether hot flushes commenced very early or in the late stages of the menopause transition also was not significantly associated with smoking.…”
Section: Discussioncontrasting
confidence: 67%
“…Although a number of studies have reported that women who smoke are more likely to report hot flushes, possibly due to the antiestrogenic effects of smoking (43, 47, 48), current smoking had no significant association with the duration of hot flushes in this cohort. Whether hot flushes commenced very early or in the late stages of the menopause transition also was not significantly associated with smoking.…”
Section: Discussioncontrasting
confidence: 67%
“…Similarly, studies in both animals and humans suggest that a short duration of hypogonadism prior to initiation of estrogen therapy is associated with beneficial effects on measures of cognition79-81 and on atherosclerotic plaque formation 82. These findings are consistent with the observed differences in treatment response between perimenopausal or recently menopausal and older postmenopausal women—the former being more likely to be symptomatic 58,59. Additionally, these findings introduce the concept of the critical window for the efficacy of estrogen therapy.…”
Section: Mood Disorders Occurring During Reproductive Aging In Womensupporting
confidence: 64%
“…13 Following baseline telephone interviews, 779 women were eligible for longitudinal studies based on having menstruated in the previous three months, having a uterus and at least one ovary, and not taking hormone therapy for menopausal symptoms or contraception: 438 (56%) agreed to participate. Compared with women who declined to participate, these women were better educated, more likely to be employed, more likely to report good health, more likely to exercise regularly, and more likely to have had a Papanicolaou smear.…”
Section: Subjectsmentioning
confidence: 99%